Strategies to increase influenza vaccine uptake among health care workers in Greece - Maragos, Antonios; Maltezou, Helena C.; Raftopoulos, Vasilios (My University, 2009)
The aim of the current study was to investigate the contribution of various strategies to increase influenza vaccine uptake among health care workers (HCWs) working in hospitals in Greece during the 2005-2006 season. A total of 132 Greek public hospitals participated in the study. The mean HCWs vaccination rate against influenza during 2005-2006 was 16.36% compared with 1.72% during the previous season. Logistic regression analysis showed that the implementation of the following strategies was significantly associated with influenza vaccination rates above the mean vaccination rate: a mobile vaccination team (OR 2.942, 95% CI 1.154-5.382, p-value 0.016) and lectures on influenza and influenza vaccine (OR 2.386, 95% CI 0.999-5.704, p-value 0.036). In conclusion, in Greece influenza vaccination rates among HCWs remain low; however, the implementation of specific strategies was associated with increased vaccine uptakes.
Keywords: Infectious Diseases